Faktor malu dalam saringan papsmear: kajian kualitatif - Azlidai, Ismail (Universiti Sains Malaysia, 2008)
Cervical cancer is the second most common cancer in women worldwide (Holland & Stewart 1990 cited from Amal & Nseem 2004). Approximately 230 thousand women die every year as a consequence of cervical cancer, and at least 80 % of these deaths occur in developing countries. Effective pap-smear screening has proven reduced the death rate. However, many previous studies found that shyness or embarrassment is one of the factors that make women refuse to go for the screening. The purpose of this study is to focus on the shyness factor among women with different socio-demographic status. Furthermore, this study also wants to identify the causes that lead to embarrassment and how to overcome it. This is a qualitative, descriptive and observational study, where the population size is 22 women aged between 18 to 65 years old that never do Pap-smear screening or do it irregularly. Data collection is a cross-sectional and using a convenience sampling and snowball effect. Findings of this study show that women with different socio-demographic status have different perception about this shyness factor that effects the women's decision to go for the screening. From the process of transcription, all the data about causes of shyness and the way to overcome it, that had been obtained from the interviews was divided according to themes. There are many causes that make women feel ashamed to go through Papsmear screening test. However, the result and the suggestions that been given by the women interviewed to overcome the shyness factors can be used in the effort to encourage women to participate in this screening in future.